Technical note: Sedidetection – deriving the nature of the sediment bottom by analyzing gait data - Kohlus, Jörn; Nowak, Friederike; Böhm, Hannah; Kagelmann, Ralf (ERDKUNDE, 2025)
In order to comply with EU guidelines for monitoring the condition of the Wadden Sea, regular transect surveys are required. Those are done by taking point sediment samples to determine the near-surface sediment composition. However, these methods are expensive and time-consuming. Remote sensing analyses provide only limited information of the first millimeters of the surface. The results are influenced by interfering signals. The application of motion analysis based on smartphone sensors was investigated in order to draw conclusions about the sediment composition along transects. The aim was to identify homogeneous sediment areas and their boundaries along the transects, thereby significantly reducing the need for traditional sediment sampling. In addition, it was examined whether qualitative statements on sediment composition can already be made with sufficient accuracy. The results show that sediment softness and area boundaries can be measured with this method, but obstacles for practical applications remain.